Development of a new tool to assess the technique of karate athletes - Ferreira, Joaquim Filipe de Freitas (2023)
This master's dissertation in sports training presents two studies. They focus on evaluating and characterizing karate athletes. Objectives: The objective of the first study was to develop and establish the validity of a technical evaluation system in karate, while the objective of the second study was to compare the technical proficiency of karate athletes across different age groups and years of experience and to examine the relationship between technical proficiency, physical fitness, and anthropometric measures. Methods: The first study used three phases to establish the validity of the technical evaluation system in karate, including expert analysis and evaluation of the observation instrument, expert evaluation of athlete performance, and reliability testing of evaluators' observations. The evaluation system assessed four common techniques in kumite competitions at different levels of proficiency. The second study used an observational crosssectional study design on a non-probabilistic convenience sample of 53 karate athletes, who were grouped according to age and years of experience. The participants were evaluated using anthropometry, physical fitness tests, and the System for the Technical Assessment of Kumite (STAK). Results: The first study found substantial to almost complete intra-rater reliability for expert and beginner athletes' evaluations, with ICC values ranging from 0.774 to 0.959. The STAK evaluation process was found to be a reliable method for assessing the success criteria of different techniques used in martial arts. However, novice athletes may require more specific and consistent evaluation criteria to improve their observation technique and refine their ability to interpret success variables in each motor action. The second study found statistically significant differences in physical fitness and technical proficiency among karate athletes of different age groups and years of experience. The technical observation instrument showed significant dependence relationships with experience, indicating the sensitivity of the instrument to differentiate the effect of experience on the quality of movement in karate athletes. Conclusion: Both studies contribute to the understanding of the technical evaluation and characterization of karate athletes. The first study establishes the validity and reliability of a technical evaluation system in karate, while the second study highlights the importance of experience in developing physical fitness and technical proficiency in karate athletes. Together, these studies provide insights into the factors that contribute to the success of karate athletes and offer a useful tool for evaluating their technical performance.